Reflections on Lament Of 30 % Matric Pass Mark In South African Schools - Sabelo Velenkosini , Msweli (International Journal of Scientific Research and Management (IJSRM), 2022)
This study examines the minimum matric pass mark of 30 percent in South African schools which has remained one of the most worrisome concerns in the education sector in terms of the quality of education delivered by schools and the number of pupils produced each year. The 30 percent figure contradicts one of Department of Basic Education's core objectives, which is to commit to quality, because 30 percent cannot reach perfection. Therefore this study's primary aim was to show reflections on lament on 30 percent matric pass mark in South African schools and the predicted end result of this 30 percent matric pass mark if it is not adjusted. The long-term goal of the project was to investigate the implications of maintaining the matriculation cut-off score of 30 percent rather than raising it to a threshold of 50 percent. This study make use of content analysis to analyse data from social media that include Facebook, twitter and blogs post. The results made it clear that there is a need for the government to take education seriously by upgrading the pass rate from 30 percent going up, the study shows that the policy should be reviewed or amended with a minimum pass mark of 50 percent in order for learners to be able to qualify for NSC on HC entrance requirements. The results shows that with at 50% pass mark learners will have various opportunities, such as continuing their education in tertiary education or entering the job market. The study suggests recommendations such as the matric learners must be awarded certificate based on 100 percent exam percentage by removing 25 percent of school based assessment as it counts to the final promotion mark in Grade 12..